2018
DOI: 10.1155/2018/5140691
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of IL-36 Family Members and IL-38 by Immune and Nonimmune Cells in Patients with Active Inflammatory Bowel Disease

Abstract: IL-1 family includes IL-38 (IL-1F10) and the subfamily of IL-36 and is the central mediators of inflammatory diseases, including pustular psoriasis, atopic dermatitis, rheumatoid arthritis, and gut inflammation. The purpose of the study was to evaluate on tissue of the patients with inflammatory bowel disease (IBD), the IL-36α, IL-36β, IL-36γ, IL-36Ra, and IL-38 gene and cell expression and its correlation with clinical activity. Patients and Methods. A cross-sectional and comparative study was performed. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 19 publications
1
64
0
3
Order By: Relevance
“…Similar to related IL‐1 family members, the role of IL‐36 in the gut is complex. While some studies have demonstrated that IL‐36 has a pro‐inflammatory role , other studies have described its role in promoting the resolution of intestinal inflammation . On the one hand, IL‐36 signalling facilitates neutrophil and inflammatory monocyte infiltration to intestinal tissues and can regulate the balance of pro‐inflammatory mucosal CD 4+ T cell subsets .…”
Section: Targeting Il‐36 In Human Diseasementioning
confidence: 99%
“…Similar to related IL‐1 family members, the role of IL‐36 in the gut is complex. While some studies have demonstrated that IL‐36 has a pro‐inflammatory role , other studies have described its role in promoting the resolution of intestinal inflammation . On the one hand, IL‐36 signalling facilitates neutrophil and inflammatory monocyte infiltration to intestinal tissues and can regulate the balance of pro‐inflammatory mucosal CD 4+ T cell subsets .…”
Section: Targeting Il‐36 In Human Diseasementioning
confidence: 99%
“…The diagnosis of UC was done by the presence of the following criteria: a history of diarrhea or blood in stools and macroscopic appearance by endoscopy and biopsy compatible with UC [6][7][8][9][10].…”
Section: Methodsmentioning
confidence: 99%
“…The control group did not take any medication. All individuals underwent colonoscopy for taking colonic biopsies before signing the written informed consent [6][7][8][9][10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two hundred nanograms of total RNA was reverse transcribed into cDNA with random hexamer primers (Roche Diagnostics, Mannheim, Germany). The methodology employed was based on the previous studies of gene expression [6][7][8] PCR ampli cation was carried out with 20 ng of cDNA, 200 nM forward, reverse primer, and Taqman Master Mix (Roche Diagnostics, Mannheim, Germany Roche Diagnostics, Mannheim, Germany) in a nal volume of 10 µl (Table 1). PCR reactions were run in a Light Cycler 480 (Roche Diagnostics, Mannheim, Germany) for 45 cycles, each cycle consists in denaturation for 15 seconds at 95°, primer annealing for 15 seconds at 55°C, and extension for 30 seconds at 72°C and cooling 30 seconds at 40°C.…”
Section: Based On the Background It Was Proposed To Analyze The Exprmentioning
confidence: 99%